2018
DOI: 10.3390/nano8060444
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Ag@Cu2O-rGO Architecture for Strong Light-Matter Interactions

Abstract: Emerging opportunities based on two-dimensional (2D) layered structures can utilize a variety of complex geometric architectures. Herein, we report the synthesis and properties of a 2D+0D unique ternary platform-core-shell nanostructure, termed Ag@Cu2O-rGO, where the reduced graphene oxide (rGO) 2D acting as a platform is uniformly decorated by Ag@Cu2O core-shell nanoparticles. Cu2O nanoparticles occupy the defect positions on the surface of the rGO platform and restore the conjugation of the rGO structure, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It is unfortunate that ZnO and TiO 2 semiconductors can only absorb and transport photons in the UV region of the solar spectrum [31]. In contrast, p-type Cu 2 O has an excellent visible light response [32,33]. A great deal of research so far has been done to improve the photocatalytic efficiencies of Au@Cu 2 O in the last few years [34].…”
Section: Introductionmentioning
confidence: 99%
“…It is unfortunate that ZnO and TiO 2 semiconductors can only absorb and transport photons in the UV region of the solar spectrum [31]. In contrast, p-type Cu 2 O has an excellent visible light response [32,33]. A great deal of research so far has been done to improve the photocatalytic efficiencies of Au@Cu 2 O in the last few years [34].…”
Section: Introductionmentioning
confidence: 99%
“…We found that there were other forms of oxygen in addition to the adsorbed oxygen and water vapor in the processing system, mainly due to the introduction of oxygen-containing functional groups onto the surface of rGO . The XPS spectrum in Figure S1 clearly shows that Ag 3d peaks at 366.87 (Ag 3d 5/2 ) and 372.88 eV (Ag 3d 3/2 ) were also observed …”
Section: Resultsmentioning
confidence: 93%
“…First, graphene oxide (GO) nanosheets were obtained by a two-step oxide graphite powder oxidation method based on the Hummers and Offeman method . Then, the improved Lee and Meisel method was used to achieve GO surface modification with Ag nanoparticles (Ag NPs) . The detailed operation was as follows: First, 1 mg of as-prepared GO nanosheets was mixed with 30 mL of deionized water, and the above mixed solution was sonicated to obtain a GO solution with great dispersion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2 O has excellent optical and electrical properties that have attracted the attention of scientists [25]. Trinitrophenol (TNP), an explosive pollutant, is distributed widely in soil and water.…”
Section: Introductionmentioning
confidence: 99%